PERLINDUNGAN TERHADAP HAK ANAK YANG MENGALAMI KEKERASAN SEKSUAL SETELAH PUTUSAN PENGADILAN NOMOR 210/Pid.B/2018/PN.Mlg TANGGAL 11 JULI 2018 (STUDI PERAN DI “OMAH AYOM” KOTA BATU, JAWA TIMUR). - Fifi Prawidiah Arini (Fakultas Hukum Universitas Islam Malang, 2020)
ABSTRACT Kota Batu has special attention to child victims of sexual crimes. This city has its own breakthrough in dealing with child victims of sexual crime which is implemented in an innovation program with the theme